A novel strategy to the formulation of carmustine and bioactive nanoparticles co-loaded PLGA biocomposite spheres for targeting drug delivery to glioma treatment and nursing care - Shufeng Yi; Fan Yang; Cunle Jie; Guiqin Zhang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Gliomas are the most common brain tumors in humans. Different chemotherapeutics are available to treat gliomas. However, they are costly and pose numerous side effects. The development of nanocomposite based on chemotherapeutic drug and metallic nanoparticle loaded with polymer could be highly useful against glioma. In this study, carmustine loaded with gold NPs and linked with PLGA-PSPE was produced as a bio-nanocomposite and its efficacy in treating glioma and burn wound were investigated. The synthesized biocomposite was characterized by biophysical techniques. It was observed that the synthesized composite was hexagonal and crystalline nature. TGA analysis showed that the particle had good combustible property. Interestingly, the Cm-Au-PLGA-PSPE composite had exhibited remarkable anti-tumor property against U251 human glioma. The flow cytometry showed a greater increase in the apoptosis rate (62.31%) of glioma cells exposed to the bio-nanocomposite. In addition, a greater reduction in the viability of U251 cells was recorded following treatment with Cm-Au-PLGA-PSPE composite. Quick healing of the heart, liver, spleen, lung and kidney tissue wounds in mouse was noticed with Cm-Au-PLGA-PSPE composite treatment. This study concludes that the newly produced Cm-Au-PLGA-PSPE composite would be a promising alternative in treating human gliomas and associated wounds with increased biomedical applications.